Current topics in cost allocation and custom API development in IBM Cognos TM1 - Fedoročko, Peter; Pour, Jan; Bothe, Ondřej; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2012)
Thesis is devoted to current trends in approaching cost allocation developed in IBM Cognos TM1 software. Concept, which was originally elaborated in my bachelor thesis, has recently experienced restrictions caused by increasing requirements on analytical tools and information they provide. Goal of the thesis is therefore to analyse causalities of emerging weaknesses, design and develop optimalized and reengineered solution answering current demands. Reqarding the quantitative evaluation of attained results, the thesis is extended with analysis of frameworks and standards dedicated to benchmarking of OLAP tools and their synthesis into own complex model. Proposed model specializes on measuring multiple OLAP applications across four main perspectives including performance, development, usability and financial benefits. Attained results prove, that reengineered model is faster, data richer, easier to use and appropriate for any organization with structured and algorithmic approach to cost allocation. Second half of the thesis focuses on extending the presentation layer to web browser, designing and developing of custom visualizations for most usual analytic tasks. Considering the absence of advanced application interface in IBM Cognos TM1, the thesis also includes theoretical analysis of current trends in API development and design of concept allowing communication and data transportation between applications and TM1 server. In the concluding section of the thesis, proposed concept is materialized into universal library developed in PHP and applied to novel allocation model. Leveraging the library, two exemplary interfaces for allocator operation and data consumption are implemented. Gained knowledge can serve as basis for development of additional components communicationg with TM1 in variety of projects or theoretical framework for API implementation in general.
Vedoucí práce: Jan Pour
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: informační systémy a technologie [obor dipl. práce]; diplomové práce; master's theses